Prezada palavra : literatura e correspondência em Josué Guimarães - Santin, Bruna (2023)
This dissertation investigates the writing and discursive movements present in the intimate epistolary of the gaucho writer Josué Guimarães. In his collection – Acervo Literário de Josué Guimarães (ALJOG/UPF), under the custody of the University of Passo Fundo, it is possible to verify more than eight thousand items, distributed in several categories, such as originals, sketches, notes, personal library, e.g. This study, however, aims to analyze the writer's active, passive, and editorial correspondence within a theory that prioritizes, among many elements, the object of artistic creation and its behind-the-scenes movements. Among the many sources for verifying the genesis of writing, it can be said include the author’s correspondence that has many personal dealings or too many personal matters and can prioritize, in his solitary dialogues, essential aspects of the life and writing of his creator. Based on Genetic Criticism, with names such as Hay (2007), Willemart (2005, 2009, 2019), Pino and Zular (2007), the objective is to frame the letter within the genetic perspective, observing its fluidity and its role in improving and following work. However, the correspondence has faces that can present in many ways, which is why there is no way to disregard, in this work, the entry into the fields of epistolary studies, which, by themselves, are primordial and complex. Theorists such as Diaz (2016) and Bouzinac (2016) contribute, therefore, evidencing, precisely, correspondence as a polymorphous and flexible terrain capable of serving many aspects, including those of genesis.